2022
DOI: 10.1186/s13018-022-02965-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects and mechanism of paeoniflorin in promoting osteogenic differentiation of MC3T3-E1

Abstract: Background The incidence of osteoporosis and osteoporotic fractures is increasing every year. Traditional Chinese Medicine (TCM) can shed new light on the treatment of osteoporosis. This study aimed to explore the role and mechanism of paeoniflorin in promoting osteogenic differentiation of an osteoblast precursor cell line (MC3T3-E1). Methods MC3T3-E1 cells were cultured in osteogenic induction medium (OIM) and OIM combined with different concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Radix Paeoniae Alba containing Paeoni orin has been widely used in the treatment of osteoporosis. Paeoni orin treatment of osteoporosis can be divided into two general directions: inhibiting osteoclast activity [70] and improving osteoblast activity [71,72], It slows bone resorption by inhibiting osteoclast activity and promotes bone formation by increasing osteoblast activity. Corydalis Yanhusuo contains Tetrahydropalmatine, Experimental studies in vivo and in vitro have shown that Tetrahydropalmatine inhibits osteoclast formation by inhibiting NF-κB and MAPK pathways [73].…”
Section: Discussionmentioning
confidence: 99%
“…Radix Paeoniae Alba containing Paeoni orin has been widely used in the treatment of osteoporosis. Paeoni orin treatment of osteoporosis can be divided into two general directions: inhibiting osteoclast activity [70] and improving osteoblast activity [71,72], It slows bone resorption by inhibiting osteoclast activity and promotes bone formation by increasing osteoblast activity. Corydalis Yanhusuo contains Tetrahydropalmatine, Experimental studies in vivo and in vitro have shown that Tetrahydropalmatine inhibits osteoclast formation by inhibiting NF-κB and MAPK pathways [73].…”
Section: Discussionmentioning
confidence: 99%
“…In early 1998, the U.S. Food and Drug Administration (FDA) approved the sale of paeoniflorin. 66 Paeoniflorin has attracted much attention worldwide owing to its multiple positive effects on alleviating liver diseases, including cholestasis, liver fibrosis, hepatocellular carcinoma, and NAFLD. 67 In a NAFLD animal model, Zhang et al 68 first examined these pharmacological effects in HFD-fed male C57BL/6J mice from a comprehensive perspective.…”
Section: ■ Iridoid Glycosidementioning
confidence: 99%
“…Paeoniflorin, a kind of white powder mainly derived from the root of the Chinese herb Paeonia lactiflora, is a water-soluble pinane monoterpenoid with a cage-like pinnae skeleton. In early 1998, the U.S. Food and Drug Administration (FDA) approved the sale of paeoniflorin . Paeoniflorin has attracted much attention worldwide owing to its multiple positive effects on alleviating liver diseases, including cholestasis, liver fibrosis, hepatocellular carcinoma, and NAFLD .…”
Section: Iridoid Glycosidementioning
confidence: 99%
“…Similarly, Dendropanax morbifera increased downstream ALP, OPN, OCN, and RUNX2 via BMP2/p38 MAPK/JNK and SMAD1/5/9 signaling pathways [17]. In addition, Panax ginseng [18] and paeoniflorin [19] have also been shown to promote osteoblast differentiation and bone formation.…”
Section: Introductionmentioning
confidence: 97%